Peran Teknologi dan Media Sosial dalam Membentuk Dinamika Kesehatan Mental Berdasarkan Perspektif Islam - Feri Julhamdani; Elis Trianti; Tarsono Tarsono; Ulfiah Ulfiah; Heryana Nugraha (Journal on Education, 2024)
This research aims to explore the role of technology and social media in shaping mental health dynamics based on an Islamic perspective. The research method used is literature study, the main focus is aimed at an in-depth understanding of the impact of the use of modern technology and interaction on social media on aspects of mental health. Involving a synthesis of information from various literature sources, this research seeks to identify behavioral patterns, trends, and key findings that can provide in-depth insight into the contribution of technology and social media to mental health based on an Islamic perspective. The results of this literature study can form the basis for a more comprehensive understanding of how this phenomenon develops over time and how it can shape overall mental health dynamics. The implications of this research are able to provide guidance for the development of more informed intervention and policy approaches to improve the psychological well-being of adolescents in the context of technology and social media